2014
DOI: 10.1016/j.jaip.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Anaphylaxis to Red Meat Masquerading as Idiopathic Anaphylaxis

Abstract: Anaphylaxis is traditionally recognized as a rapidly developing combination of symptoms often including hives and hypotension or respiratory symptoms. Furthermore, when a specific cause is identified, exposure to this cause is usually noted to have occurred within minutes to 2 hours before the onset of symptoms. This case is of a 79 year-old female who developed a severe episode of anaphylaxis 3 hours after eating pork. Prior to 2012, she had not experienced any symptoms after ingestion of meat products. Delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 35 publications
(39 reference statements)
0
44
0
Order By: Relevance
“…14 Although low-density and very low-density lipoproteins can cause basophils to upregulate, evidenced by increased CD63 activation, development of symptoms is believed to be due to mast cell degranulation rather than basophil activation. 12,14 Basophil activation correlates with onset of clinical symptoms and can serve as a marker for the presence of alpha-gal in the bloodstream. 12 …”
Section: Delayed Reactionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Although low-density and very low-density lipoproteins can cause basophils to upregulate, evidenced by increased CD63 activation, development of symptoms is believed to be due to mast cell degranulation rather than basophil activation. 12,14 Basophil activation correlates with onset of clinical symptoms and can serve as a marker for the presence of alpha-gal in the bloodstream. 12 …”
Section: Delayed Reactionmentioning
confidence: 99%
“…Onset is typically in adults, although children are not excluded. 4,14 Kennedy et al 18 identified 45 pediatric patients with the allergy. In the United States, red meat typically includes beef, pork, and lamb.…”
Section: Diagnostic Approachmentioning
confidence: 99%
See 3 more Smart Citations